PENGARUH MODEL RADEC TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS IV SDN SUKODONO II (MATERI: WUJUD ZAT DAN PERUBAHANNYA) - Maghfiroh; Muhammad Assegaf Baalwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the impact of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on the science literacy skills of fourth-grade students at SDN Sukodono II. The research was motivated by students' difficulties in understanding the states of matter due to conventional teaching methods and limited use of interactive media. A pre-experimental one-group pretest-posttest design was employed involving 30 students. The literacy test was developed based on PISA indicators and validated using expert judgment and Cronbach’s Alpha (α = 0.771). Data analysis using the Paired Sample T-Test showed a statistically significant difference between pretest (M = 10.47, SD = 3.15) and posttest (M = 15.83, SD = 4.50) scores, with t(29) = -8.781, p < 0.001. The results indicate that the RADEC model significantly improves students’ science literacy. This model is recommended as an effective, interactive, and contextual learning strategy for primary education.